Growth changes after gluteen free diet in pediatric celiac patients: a literature-review - Ghiselli, Alessia; Bizzarri, Barbara; Gaiani, Federica; Semeraro, Francesca; Iuliano, Silvia; Di Mario, Francesco; Nouvenne, Antonio; Kayali, Stefano; de 'Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
Background: Celiac disease is an auto-immune disorder characterized by clinical manifestations that appear in genetically predisposed subjects after gluten ingestion. In the last years, there has been a progressive change in clinical manifestations. Our aim was to evaluate the nutritional status of children with celiac disease at diagnosis and how the gluten-free diet (GFD) influences their growth. Methods: A search on PubMed/Medline was performed using “celiac disease”, “body mass index” and “children” as key words. Medline, Scopus, PubMed publisher and Google Scholar were searched as well. We selected clinical studies describing the nutritional status of patients before and after GFD using indicators like height, weight, BMI, skeletal age. We excluded papers referred to adult population or in which other diseases were related to celiac disease. Also literature-reviews were excluded. Results: From 1999 to 2018, 10 studies were found. Overall, 1383 patients in pediatric age were evaluated for their nutritional status at diagnosis of celiac disease and after a variable period from 1 to 17 years of GFD. Indicators considered were height, weight, BMI and skeletal age. Conclusions: the nutritional status of celiac patients at diagnosis is variable including an increasing number of overweight and obese. GFD has a beneficial impact on growth changes determining a correction of BMI distribution towards a Gaussian shape